Fundamental Rights and Climate Change: Exploring New Perspectives and Corresponding Remedies (Wydawnictwo Księgarnia Akademicka, 2025)
For many years legal thought and practice focused on the general concept of environmental rights as a legal tool meant to enforce the human right to a healthy and sustainable environment. Whilst there is an undeniable link between human rights and climate change, as illustrated notably by the global phenomenon of the climate change litigation, this monograph focuses on the growing role of potential, sectoral fundamental rights and tailored remedies available in the EU legal order in absence of a substantive fundamental right to a healthy environment in EU law. Against the background of the European Green Deal and its ambitious climate-neutrality goal by 2050, the book echoes the sustainability-based approach and its limits. Contributors analyse two interrelated perspectives. On the one hand, authors explore the procedural dimension by discussing the climate litigation and the limits of the concept of human environmental rights, state liability for loss and damage caused to individuals as a result of breaches of EU law, national remedies available in case of bad condition of the environment as well as the limits of the public interest litigation and challenges related to climate claims against private actors in national law. On the other hand, contributors discuss substantive aspects from a global perspective of food insecurity, soil monitoring and resilience as well as digitalisation, green skills and climate-induced migration. With insights from leading experts, this work highlights the evolving tensions and expectations within the EU legal framework. Essential for legal practitioners, policymakers, academics, and students of law and administration, this book offers a comprehensive exploration of the intersection between sustainability, climate action, and the protection of fundamental rights in EU law.